Exemplo de uma sucessão faunística durante a decomposição em um amontoado de folhiço - Guimarães, Anthony Érico (1984)
Aiming at the establishment of an existing succession between the soil mesofauna developing groups during the decomposition of the litter, systematic sampling were conducted in a previously selected biotope – called by the author “fosso de folhiço” – during 12 consecutive months (June 1977 to July 1978). Throughout 360 days of studies, we identified 19 faunistic groups, adding up a total of 79 916 specimens. To accomphish that, there were made 24 samplings with intervals of 15 days. From the data obtained, we realize that, in the opportunity, the most directly related groups with decomposition of the litter were respectively: Collembola, Isopoda and Acarina. The 19 faunistic groups found were taxionomically defined at level order. Among them, Collembola deserved a more detailed analysis and, consequently, their specimens are identified in accordance with the corresponding genus, 17 in the whole. Out of these, we considered Lepidocyrtus and Isotoma as the most abundant. We have established the periods of activity of each group in the succession and we have discussed the diversity of biological forms found in the relation to the period of the decomposition process in which they have occurred.